Nitrogen fixation by the Native Azospirillum spp. Ssolated from Rhizosphere and Non-Rhizosphere of foxtail Millet - Raffi, Mokula Md.; Charyulu, P.B.B.N. (Asian Journal of Biological and Life Sciences, 2012)
Experiments were conducted to isolate Azospirillum spp. from the rhizosphere and non-rhizosphere soil of foxtail millet grown in native black loamy soils of Anantapur district. A total of 100 strains of Azospirillum were isolated and grown on semi-solid nitrogen-free bromothymol blue malate semisolid malate agar (Nfb), purified and tested for nitrogen fixing abilities, only 56 strains of Azospirillum spp. strains showed nitrogen fixing ability, -1 out of which 20 strains fixed nitrogen efficiently. Azospirillum strains varied in their nitrogen-fixing abilities ranging from 2.95 to 12.4 mg g malate. All the strains were identified as Azospirillum lipoferum. These strains when tested for IAAproduction, all produced IAA.